Continuous medium ultraviolet light emitting material and preparation method thereof

CN118599525BActive Publication Date: 2026-10-09陈连平
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410693780.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-31
Publication Date
2026-10-09
Estimated Expiration
2044-05-31

AI Technical Summary

Technical Problem

因此,现有的掺铈碱土族铝酸盐材料不能被254纳米的紫外光高效地激发并发射出很强的中紫外光

Benefits of technology

[0036] This invention improves the element ratio, controls the sintering temperature between 1400 and 1700°C, and controls the holding time to 2 to 48 hours to sinter a continuous mid-ultraviolet luminescent material with a triclinic phase structure; the luminescence index value is significantly improved compared with the monoclinic phase structure material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118599525B_ABST
    Figure CN118599525B_ABST
Patent Text Reader

Abstract

The application discloses a continuous medium-ultraviolet light emitting material and a preparation method thereof. x Al y O (x+1.5y+1.5z) :Ce z , wherein M represents a combination of one or more elements of Sr, Ca, Ba or Mg, 0
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a continuous ultraviolet light-emitting material, belonging to the field of novel functional materials, and is particularly suitable for developing into products such as high-efficiency ultraviolet LEDs and full ultraviolet light sources. Background Technology

[0002] There are two main ways to obtain ultraviolet light: one is to use an ultraviolet LED chip to emit light and produce ultraviolet light of a specific wavelength; the other is to use gas discharge, such as mercury lamps and xenon lamps that use rarefied gas discharge.

[0003] Current ultraviolet (UV) LEDs primarily use AlGaN, InAlGaN, or MgZnO as the core material for light emission. However, UV LEDs based on AlGaN, InAlGaN, or MgZnO suffer from the following drawbacks: First, the emission spectrum is an isolated narrow band (often less than 10 nm bandwidth) with peak wavelengths in the 250–420 nm range, resulting in a discontinuous emission spectrum. Second, the emission wavelength of current UV LED chips is highly dependent on the fabrication process, making wavelength control difficult. Third, the quantum yield of current UV LED chips is very low; for example, the quantum yield of a 365 nm LED produced by Nitride Semiconductors in Japan is approximately 14.7%. The shorter the emission wavelength, the lower the quantum yield.

[0004] Xenon lamps emit a continuous spectrum, primarily consisting of visible and near-infrared light, with ultraviolet radiation comprising only a small portion. This means that the energy used to generate ultraviolet radiation accounts for only a small fraction of the electrical energy consumed. Furthermore, xenon gas is a rare gas and relatively expensive, making it unsuitable for widespread use in everyday sterilization and lighting applications.

[0005] The characteristic spectral lines of mercury vapor discharge radiation are extremely narrow line lines, with main spectral line wavelengths of 253.7, 365, 405, 435, 545, 578, and 763 nm. While ultraviolet light can be obtained by exciting some phosphors with ultraviolet light at a wavelength of 254 nm, the excitation bands of most luminescent materials do not match the mercury lamp spectral lines; moreover, the emission spectra of most phosphors are not in the ultraviolet band, especially lacking the mid-ultraviolet wavelengths of 280–320 nm and the far-ultraviolet wavelengths of 260–280 nm.

[0006] To date, reported inorganic luminescent materials capable of emitting ultraviolet light include (Ca,Zn)3(PO4)2:Tl, BaSi2O5:Pb, and LaMgAl. 11 O 19 :Ce, SrAl2O4:Ce, CaAl2O4:Ce and BaAl2O4:Ce.

[0007] The calcium orthophosphate matrix (Ca,Zn)3(PO4)2:Tl can emit ultraviolet light with a wavelength of 280-350 nm and a peak wavelength of 310 nm when excited by 253.7 nm ultraviolet light. It can be used to manufacture health light lamps.

[0008] The barium disilicate-based BaSi2O5:Pb absorbs 254 nm ultraviolet light and produces ultraviolet light with a center wavelength of 350 nm, and a spectral range of 310–400 nm. It can be used in the manufacture of tanning lamps.

[0009] Because thallium is a highly toxic element and lead is a highly toxic element, (Ca,Zn)3(PO4)2:Tl and BaSi2O5:Pb are difficult to widely use due to the increasing emphasis on environmental protection and safety.

[0010] Hexagonal LaMgAl 11 O 19 Ce absorbs 254 nm ultraviolet light and produces near-ultraviolet light, with the peak wavelength of the emission spectrum between 350 and 360 nm and a quantum efficiency of up to 60%.

[0011] Researchers such as Foke KE et al. have shown that the SrAl₂O₄:Ce powder synthesized by combustion has a monoclinic structure, with an excitation spectrum wavelength range of 240–350 nm, a peak excitation wavelength of 330 nm, and relative excitation intensities of 0.20 and 0.16 at 258 nm and 278 nm, respectively. Under 330 nm ultraviolet light excitation, the emission spectrum of SrAl₂O₄:Ce powder has a wavelength range of 340–450 nm, with a peak emission wavelength of 360 nm. This emission spectrum can be decomposed into two sub-emission bands with center wavelengths of 360 nm and 380 nm, respectively.

[0012] Researchers such as Gedekar KA synthesized a hexagonal BaAl₂O₄:Ce powder via combustion. The peak wavelength of the excited spectrum was 308 nm, and the relative excitation intensity at 254 nm was approximately 0.16. Under 308 nm ultraviolet light excitation, the emission spectrum of the BaAl₂O₄:Ce powder was a broadband spectrum with wavelengths between 340 and 600 nm, and the peak emission wavelength was 386 nm.

[0013] Researchers such as Gedekar KA synthesized a monoclinic SrAl₂O₄:Ce powder via combustion. The peak wavelength of the excited spectrum was 331 nm, with a relative intensity of approximately 0.13 at 266 nm and approximately 0.01–0.02 at 254 nm. Under 331 nm ultraviolet light excitation, the SrAl₂O₄:Ce powder exhibited a broadband emission spectrum with wavelengths between 340 and 450 nm, and a peak emission wavelength of 371 nm.

[0014] Researchers including Gedekar K.A. synthesized CaAl2O4:Ce powder via combustion method, which has a monoclinic structure. The peak wavelength of its excitation spectrum is 300 nm, and the relative intensity at 250 nm is about 0.02. Excited by 300 nm ultraviolet light, the emission spectrum of CaAl2O4:Ce powder is a broad band with a wavelength ranging from 330 to 450 nm, which has a single-peak structure and the peak emission wavelength is 370 nm.

[0015] Researchers including Diaz-Torres L.A. treated SrAl2O4:Ce synthesized by combustion method 3+ powder with heat treatment at 1150°C for 6 hours. The heat-treated SrAl2O4:Ce powder has a monoclinic structure, the optimal excitation wavelength is between 320 and 355 nm, and there is no obvious excitation peak at 254 nm. Excited by 355 nm ultraviolet light, the emission spectrum of SrAl2O4:Ce powder is a broad band with a wavelength ranging from 370 to 660 nm, and the peak emission wavelength is 427 to 438 nm.

[0016] Researchers including Nakauchi Daisuke grew SrAl2O4:Ce single crystals via the floating zone method. The excitation spectrum wavelength of the SrAl2O4:Ce single crystal ranges from 240 to 350 nm, the peak excitation wavelength is 325 nm, and the relative intensities at 280 nm and 254 nm are 0.50 and 0.19 respectively. Excited by 254 nm ultraviolet light, the SrAl2O4:Ce single crystal originates from Ce 3+ which emits bright blue light through 5d-4f transition. When the SrAl2O4:Ce single crystal is excited by 320 nm ultraviolet light, the wavelength of its emission spectrum ranges from 340 to 450 nm, and the peak emission wavelength is around 380 nm. When excited by 330 nm ultraviolet light, the quantum yields of SrAl2O4:Ce single crystals with Ce doping contents of 0.5%, 1.0% and 2% are 13%, 39% and 14% respectively.

[0017] We prepared phosphor with a monoclinic structure and chemical composition of Sr 0.94 Al2O4:Ce 0.04 via high-temperature solid-phase sintering method, and tested its luminescence quantum yield using an Edinburgh FLS980 fluorescence spectrometer. According to calculation, the luminescence quantum yields under excitation of 254 nm and 316 nm ultraviolet light are 0.09% and 2.20% respectively. This indicates that monoclinic Sr (1-1.5x) Al2O4:Ce x (0<x<0.06) almost does not emit light when excited by 254 nm ultraviolet light; even when excited by 316 nm ultraviolet light, the luminous efficiency of this phosphor is still very low.

[0018] Therefore, it can be seen that the peak wavelength of the excitation spectrum of existing cerium-doped alkaline earth aluminate materials is in the range of 300–340 nm, and its relative excitation intensity at 254 nm is generally at the level of a few percent (with a few exceptions reaching 0.16–0.20). Moreover, its peak wavelength of emission spectrum is in the range of 350–440 nm, and it has no obvious emission peak in or near the mid-ultraviolet light band (280–320 nm) (320–335 nm). Therefore, existing cerium-doped alkaline earth aluminate materials cannot be efficiently excited by 254 nm ultraviolet light and emit strong mid-ultraviolet light. Summary of the Invention

[0019] To address the problems existing in current ultraviolet (UV) luminescent materials, the present invention aims to provide a triclinic structure that can efficiently convert 254 nm UV light into continuous mid-UV light. Compared to existing UV luminescent materials, the material disclosed in this invention does not contain highly toxic or extremely toxic elements, and under excitation by 254 nm UV light, it can efficiently emit continuous UV light with a wavelength of 280–380 nm, exhibiting a distinct emission peak in the 280–335 nm range. Furthermore, the material obtained using the material composition and preparation method disclosed in this invention has a triclinic structure, significantly different from the crystal structures of known alkaline earth aluminates. Typical known alkaline earth aluminates mainly refer to monoclinic phases (JCPDS PDF#74-0794), orthorhombic phases (JCPDS PDF#76-0839), or monoclinic phases (JCPDS PDF#70-1479), and SrAl2O4 phases with chemical compositions of SrAl2O4. 12 O 19 The hexagonal phase of MgAl2O4 (JCPDS PDF#80-1195), the cubic phase of MgAl2O4 (JCPDS PDF#77-0435), and Mg 0.4 Al 2.4 Cubic phase of O4 (JCPDS PDF#84-0378), monoclinic phase of CaAl2O4 (JCPDS PDF#70-0134), monoclinic phase of CaAl4O7 (JCPDS PDF#72-0767), CaAl 12 O 19 The hexagonal phase of BaAl2O4 (JCPDS PDF#84-1613), the hexagonal phase of BaAl2O4 (JCPDS PDF#72-0387), and Ba 1.157 Al 10.686 O 17.157 The hexagonal phase (JCPDS PDF#83-0271), etc.

[0020] To achieve the above objectives, the present invention adopts the following technical solution:

[0021] A continuous mid-ultraviolet luminescent material, wherein the crystal structure of the luminescent material belongs to the triclinic crystal system.

[0022] Furthermore, the general chemical formula is M x Al y O (x+1.5y+1.5z) :Ce z Where M represents a combination of one or more elements selected from Sr, Ca, Ba, or Mg, 0 <z<0.05y,0.04≤(x / y)≤0.25。

[0023] Furthermore, the general chemical formula is M x Al y O (x+1.5y+1.5z) :Ce z Where M represents a combination of one or more elements from Ca, Ba, or Mg with Sr, 0 <z<0.05y,0.04≤(x / y)≤0.25。

[0024] Furthermore, the general chemical formula is Sr x Al y O (x+1.5y+1.5z) :Ce z , of which 0 <z<0.05y,0.04≤(x / y)≤0.25。

[0025] Furthermore, when excited by 254 nm ultraviolet light, it can emit a continuous ultraviolet spectrum with wavelengths between 280 and 380 nm.

[0026] Furthermore, when excited by 254 nm ultraviolet light, it can emit continuous mid-ultraviolet light with a significant emission peak in the 280–320 nm band, or a significant emission peak in the 320–335 nm band, and the relative emission intensity at 320 nm reaches more than 60% of the peak intensity of the emission spectrum (280–480 nm).

[0027] Furthermore, when excited by 254 nm ultraviolet light, it can emit continuous mid-ultraviolet light, with an independent emission peak in the 280–320 nm wavelength range.

[0028] This invention also discloses a method for preparing the above-mentioned continuous mid-ultraviolet luminescent material, comprising the following steps:

[0029] Step S1: Prepare a mixture of metal compound powders according to the stoichiometric ratio of the metal elements in the above chemical formula.

[0030] Step S2: Measure an appropriate volume of anhydrous ethanol and pour it into the mixture obtained in step S1. Wet grinding or ball milling (add an appropriate proportion of alumina grinding balls) is performed for a certain period of time. Then, separation is carried out to obtain a slurry of the mixture. The slurry is dried in a drying oven at 100-200℃ for a certain period of time to obtain the mixture before calcination.

[0031] Step S3: The mixture before calcination is loaded into a corundum crucible and placed in an atmosphere furnace for sintering. During the calcination process, a reducing atmosphere such as hydrogen, ammonia, or a hydrogen-nitrogen mixture is used for protection (when a hydrogen-nitrogen mixture is used, the volume ratio of hydrogen is not less than 5%). The sintering temperature is controlled between 1400 and 1700°C, and the holding time is controlled between 2 and 48 hours.

[0032] Step S4: The sintered product is crushed, ground, and sieved through a standard sieve to obtain the continuous mid-ultraviolet light luminescent material.

[0033] Furthermore, the reducing atmosphere protection gas is hydrogen, ammonia, or a hydrogen-nitrogen mixture (hydrogen volume ratio not less than 5%).

[0034] Furthermore, the standard sieve is a 50-mesh to 800-mesh standard sieve.

[0035] Furthermore, it is added to fluorescent material products in powder, bulk, and thin film states.

[0036] This invention improves the element ratio, controls the sintering temperature between 1400 and 1700°C, and controls the holding time to 2 to 48 hours to sinter a continuous mid-ultraviolet luminescent material with a triclinic phase structure; the luminescence index value is significantly improved compared with the monoclinic phase structure material. Attached Figure Description

[0037] Figure 1 Its chemical composition is Sr 0.5 Al2O 3.56 :Ce 0.04 A comparison of the X-ray diffraction characteristic spectrum of the sample with the standard spectra of the monoclinic phase of SrAl2O4 (JCPDS PDF#74-0794) and the monoclinic phase of SrAl4O7 (JCPDS PDF#70-1479) (2θ ranges from 5 to 70°).

[0038] Figure 2 Its chemical composition is Sr 0.5 Al2O 3.56 :Ce 0.04 Excitation spectrum of the sample (emission wavelength 363 nm);

[0039] Figure 3 Tri-phase Sr 0.5 Al2O 3.56 :Ce0.04 Sample and monoclinic Sr 0.94 Al2O4:Ce 0.04 Comparison of emission spectra of control samples (excitation wavelength 254 nm);

[0040] Figure 4 Its chemical composition is Sr 0.94 Al2O4:Ce 0.04 The quantum yield calculation results of the sample (excitation wavelength of 254 nm);

[0041] Figure 5 Its chemical composition is Sr 0.5 Al2O 3.56 :Ce 0.04 The quantum yield calculation results of the sample (excitation wavelength of 254 m);

[0042] Figure 6 Its chemical composition is Sr 0.3 Al2O 3.36 :Ce 0.04 Sample and monoclinic Sr 0.94 Al2O4:Ce 0.04 Comparison of emission spectra of control samples (excitation wavelength 254 nm);

[0043] Figure 7 Its chemical composition is Sr 0.16 Al2O 3.22 :Ce 0.04 The X-ray diffraction characteristic spectrum and chemical composition of the sample are SrAl 12 O 19 Comparison diagram of the standard spectrum of the hexagonal phase (JCPDS PDF#80-1195) (2θ is 25-55°);

[0044] Figure 8 Tri-phase Sr 0.16 Al2O 3.22 :Ce 0.04 Sample and monoclinic Sr 0.94 Al2O4:Ce 0.04 Comparison of emission spectra of control samples (excitation wavelength 254 nm);

[0045] Figure 9 Tri-phase Sr 0.16 Al2O 3.22 :Ce 0.04 Excitation spectrum of the sample (emission wavelength 309 nm);

[0046] Figure 10 Its chemical composition is Sr 0.1 Al2O 3.16 :Ce0.04 Sample and monoclinic Sr 0.94 Al2O4:Ce 0.04 Comparison of emission spectra of control samples (excitation wavelength 254 nm);

[0047] Figure 11 Its chemical composition is Ca 0.5 Al2O 3.53 :Ce 0.02 Sample and monoclinic Ca 0.97 Al2O4:Ce 0.02 Comparison of emission spectra of control samples (excitation wavelength 254 nm);

[0048] Figure 12 Its chemical composition is Ca 0.3 Al2O 3.33 :Ce 0.02 Sample and monoclinic Ca 0.97 Al2O4:Ce 0.02 Comparison of emission spectra of control samples (excitation wavelength 254 nm);

[0049] Figure 13 Its chemical composition is Ca 0.2 Al2O 3.23 :Ce 0.02 The X-ray diffraction characteristic spectrum and chemical composition of the sample are CaAl12O 19 Comparison diagram of the standard spectrum of the hexagonal phase (JCPDS PDF#84-1613) (2θ is 25-70°);

[0050] Figure 14 Its chemical composition is Ca 0.2 Al2O 3.23 :Ce 0.02 Sample and monoclinic Ca 0.97 Al2O4:Ce 0.02 Comparison of emission spectra of control samples (excitation wavelength 254 nm);

[0051] Figure 15 Its chemical composition is Ca 0.08 Al2O 3.11 :Ce 0.02 The X-ray diffraction characteristic spectrum and chemical composition of the sample are CaAl12O 19 Comparison diagram of the standard spectrum of hexagonal phase (JCPDS PDF#84-1613) (2θ is 5~70°);

[0052] Figure 16 Its chemical composition is Ca 0.08 Al2O 3.11 :Ce 0.02Sample and monoclinic Ca 0.97 Al2O4:Ce 0.02 Comparison of emission spectra of control samples (excitation wavelength 254 nm);

[0053] Figure 17 Its chemical composition is Sr 0.4 Ba 0.1 Al2O 3.56 :Ce 0.04 A comparison of the X-ray diffraction characteristic spectrum of the sample with the standard spectra of the hexagonal phase of BaAl2O4 (JCPDS PDF#72-0387) and the monoclinic phase of SrAl4O7 (JCPDS PDF#70-1479) (2θ is 5-60°). Figure 18 The chemical composition is (Sr) 0.4 Ba 0.1 Al2O 3.56 :Ce 0.04 Sample and monoclinic Sr 0.94 Al2O4:Ce 0.04 Comparison of emission spectra of control samples (excitation wavelength 254 nm);

[0054] Figure 19 Its chemical composition is Sr 0.31 Mg 0.14 Al2O 3.51 :Ce 0.04 Sample and monoclinic Sr 0.94 Al2O4:Ce 0.04 Comparison of emission spectra of control samples (excitation wavelength 254 nm);

[0055] Figure 20 Its chemical composition is Mg 0.05 Ca 0.14 Sr 0.23 Ba 0.03 Al2O 3.51 :Ce 0.04 Sample and monoclinic Sr 0.94 Al2O4:Ce 0.04 Emission spectra comparison of control samples (excitation wavelength 254 nm). Detailed Implementation

[0056] To facilitate the discussion of the mid-ultraviolet luminescence performance of the triclinic structure luminescent material of the present invention in specific embodiments, Table 1 lists the chemical compositions conforming to the chemical formula M. x Al y O (x+1.5y+1.5z) :Ce zInformation such as the peak wavelength of the emission spectrum and the integrated area of the emission spectrum within 280 to 320 nanometers of the material (where M is elements Sr, Ca, and element combinations of SrBa, SrMg and SrCaMgBa, 0<z<0.05y, 0.04y≤x≤0.25y) when excited by 254 nanometer ultraviolet light. The relevant emission spectrum information of the control samples is also listed in Table 1. The crystal structure of the control samples belongs to the monoclinic system. In the table, "I 320 " represents the emission spectrum counting intensity at 320 nanometers, "I max " represents the maximum counting intensity of the emission spectrum (265 to 480 nm), "I 320 / I max " represents the relative luminous intensity at 320 nanometers, "S (280~320) " represents the integrated area of the emission spectrum within the wavelength range of 280 to 320 nanometers, "S (280~320) / S (280~320,对照样品) " represents the ratio of the integrated area of the emission spectrum of a sample within 280 to 320 nanometers to the integrated area of the control sample within the same range.

[0057] Table 1 Emission spectrum information of M x Al y O (x+1.5y+1.5z) :Ce z (0<0.04y≤x≤0.25y) and control samples

[0058]

[0059] It can be seen from Table 1 that among the two control samples listed in the table, Sr 0.94 Al2O4:Ce 0.04 has a larger integrated area of the emission spectrum within 280 to 320 nanometers, that is, Sr 0.94 Al2O4:Ce 0.04 has stronger luminous capacity in the middle ultraviolet wavelength band.

[0060] By comparing the integrated areas of the emission spectrum within 280 to 320 nanometers of the samples with doping concentrations of 0.04 and 0.07 respectively in Table 1, it is concluded that when the strontium-aluminum ratio is close to 0.47, the concentration of cerium has no obvious effect on the luminous intensity; when the strontium-aluminum ratio is 0.25, the concentration of cerium has a relatively obvious effect on the luminous intensity. Therefore, the stoichiometric ratio of cerium to aluminum in the chemical formula M x Al y O (x+1.5y+1.5z) :Ce z is limited to 0 to 0.05, that is 0<z<0.05y.

[0061] It can also be seen from Table 1 that for Sr x Al yO (x+1.5y+1.5z) :Ce z and Ca x Al y O (x+1.5y+1.5z) :Ce z In terms of materials, as the x / y ratio decreases, S (280~320) It shows a trend of first increasing and then decreasing.

[0062] The preparation method of the triclinic ultraviolet luminescent material disclosed in this invention can be achieved by high-temperature solid-state sintering under a reducing atmosphere such as hydrogen, ammonia, or a hydrogen-nitrogen mixture. The sintering temperature should be controlled between 1400 and 1700°C, and the holding time can be adjusted according to the particle size and performance requirements of the product. Alternatively, the precursor of the ultraviolet luminescent material described in this invention can be synthesized first using methods such as chemical precipitation, sol-gel, combustion, and spray pyrolysis, and then the precursor is sintered at high temperature in a reducing atmosphere. Since the high-temperature solid-state sintering method is mature and easy to industrialize, the new formulation materials in the examples are all synthesized using this preparation technology.

[0063] Since the preparation methods used for each formulation material in the specific embodiments are the same, the preparation details will be described in detail here.

[0064] Cerium oxide powder (99.99% purity) produced by Qiandong Rare Earth Group Technology Co., Ltd. was used as the raw material for cerium. Other raw materials were all analytical grade, and the manufacturers and purity information are as follows: strontium carbonate (99.0% purity), barium carbonate (99.0% purity), and alumina (94.0% purity) produced by Tianjin Kemei Chemical Reagent Co., Ltd.; calcium carbonate (99.0% purity) and anhydrous ethanol (99.9% purity) produced by Xilong Scientific Co., Ltd.; and magnesium hydroxide (95.0% purity) produced by Shanghai Maclean Biochemical Co., Ltd. as the source of magnesium.

[0065] Step 1: Calculate the molecular weight based on the specific chemical elements represented by x, y, z, and M in the chemical formula of the target product.

[0066] Step 2: Calculate the weight of each raw material required for the experiment based on the molecular weight of the target product, the weight of the product, and the purity of the raw materials.

[0067] Step 3: Accurately weigh each raw material according to its calculated weight.

[0068] Step 4: After initial mixing, add an appropriate amount of anhydrous ethanol (purity 99.9%) to make a slurry; wet grinding or ball milling (add an appropriate proportion of alumina grinding balls) can be used for deep mixing for a certain period of time, and separation operation is performed after grinding or ball milling to obtain the slurry of the mixture.

[0069] Step 5: Transfer the slurry to a drying oven at 100-200°C and dry it for a certain period of time to obtain the mixture before calcination.

[0070] Step 6: After the slurry is completely dry, remove the powder and put it into the corundum boat.

[0071] Step 7: Place the corundum boat filled with powder into the tubular atmosphere furnace and close the flanges at both ends of the tubular atmosphere furnace.

[0072] Step 8: Use a vacuum pump to perform a vacuuming operation on the tubular atmosphere furnace.

[0073] Step 9: Control the flow rates of hydrogen (99.99% purity), ammonia, and nitrogen (99.99% purity) using a gas flow meter. Open the atmosphere furnace inlet valve and, when the furnace reaches positive pressure, open the exhaust valve to release the exhaust gas. The exhaust gas is then combusted using an automatic ignition device and released into the air. If the exhaust gas cannot be combusted, it is guided to the outside for discharge using a stainless steel pipe.

[0074] Step 10: Set the sintering process. The sintering temperature should be controlled between 1400 and 1700℃. Set the holding time to 2 to 48 hours. The heating rate can be adjusted according to the product performance requirements and the heating performance of the atmosphere furnace. The holding time can be adjusted according to the product particle size and performance requirements. Allow the product to cool naturally after the holding time is completed.

[0075] Step 11: When the furnace temperature drops below 200°C, turn off the hydrogen or ammonia gas and only introduce nitrogen gas for a certain period of time.

[0076] Step 12: When the furnace temperature drops to near room temperature, open the flange of the tubular atmosphere furnace, take out the powder and ball mill or grind it until it passes smoothly through a 120-mesh standard sieve. Collect the powder that passes through the sieve to obtain the sample, and seal and store it.

[0077] The continuous mid-ultraviolet light-emitting material of the present invention can be prepared by following steps 1 to 12 above.

[0078] To better explain the present invention, a detailed description will be provided below with reference to some specific implementation examples.

[0079] Example 1

[0080] A triclinic luminescent material that can be excited by 254 nm ultraviolet light and emit continuous mid-ultraviolet light, its chemical composition is Sr 0.5 Al2O 3.56 :Ce 0.04 The material with this composition can be prepared by following steps 1 to 12 described above. In this embodiment, a hydrogen atmosphere is used, the sintering temperature is 1650℃, and the holding time is 48 hours.

[0081] Sr 0.5 Al2O3.56 :Ce 0.04 The X-ray diffraction characteristics of the material (2θ = 5–70°) are shown in the attached figure. Figure 1 As shown. The Sr / Al ratio of SrAl4O7 is consistent with that of the sample (both are 0.25), therefore, the X-ray diffraction standard spectrum of monoclinic SrAl4O7 (JCPDS PDF#70-1479) is used as the reference spectrum. In addition, the standard diffraction spectrum of monoclinic SrAl2O4 (JCPDS PDF#74-0794) is also used as the reference spectrum, as shown. Figure 1 As shown.

[0082] from Figure 1 It can be seen that Sr 0.5 Al2O 3.56 :Ce 0.04 The X-ray diffraction pattern of the material still exhibits three strong diffraction lines in the mid-to-high angle region where 2θ is greater than 50°. The relative intensities of these lines near 58.5°, 60.0°, and 67.2° are 33%, 49%, and 41%, respectively. In contrast, the monoclinic phases of SrAl2O4 (JCPDS PDF#74-0794) and SrAl4O7 (JCPDS PDF#70-1479) show no diffraction lines with a relative intensity greater than 20% in the mid-to-high angle region where 2θ is greater than 50°. At 2θ values ​​of 8.0°, 15.8°, 29.5°, 30.4°, and 33.1°, Sr... 0.5 Al2O 3.56 :Ce 0.04 The X-ray diffraction patterns of the materials show diffraction lines with relative intensities greater than 10%, while the monoclinic phases of SrAl2O4 (JCPDS PDF#74-0794) and SrAl4O7 (JCPDS PDF#70-1479) show no obvious diffraction lines at these angles. The first and fourth strongest diffraction peaks of the SrAl4O7 monoclinic phase (JCPDS PDF#70-1479) correspond to 2θ values ​​of 25.09° and 14.17°, respectively, while Sr... 0.5 Al2O 3.56 :Ce 0.04 The X-ray diffraction pattern of the material does not show any diffraction peaks near either of these two angles.

[0083] Further analysis revealed that within the range of 2θ ranging from 31.0° to 33.5°, Sr 0.5 Al2O 3.56 :Ce 0.04The X-ray diffraction pattern of the material shows five relatively strong diffraction peaks, while the monoclinic phases of SrAl₂O₄ (JCPDS PDF#74-0794) and SrAl₄O₇ (JCPDS PDF#70-1479) show only two and three diffraction peaks with relative intensities greater than 1%, respectively, within the same angular range, and both exhibit significant angular deviations. Within the 2θ range of 28.0–31.0°, Sr… 0.5 Al2O 3.56 :Ce 0.04 The X-ray diffraction pattern of the material has 7 very strong diffraction peaks (all with relative intensities of around 20%), while the monoclinic phase of SrAl2O4 (JCPDSPDF#74-0794) and the monoclinic phase of SrAl4O7 (JCPDSPDF#70-1479) only have 3 and 2 diffraction peaks respectively in this angle range.

[0084] After calibration and calculation, the chemical composition disclosed in this invention is Sr. 0.5 Al2O 3.56 :Ce 0.04 The crystal structure of the material belongs to the triclinic crystal system, with space group P1[1], and lattice constants a, b and c are 12.2258, 5.0670 and 12.2258, respectively. α, β, and γ are 60.0°, 68.7°, and 92.2°, respectively, and the unit cell volume is... In addition, the space group of the monoclinic phase with chemical composition SrAl2O4 (JCPDS PDF#74-0794) is P21[4], and the lattice constants a, b and c are 8.4470, 8.8160 and 8.8160 respectively. α, β, and γ are 90.0°, 93.4°, and 90.0°, respectively, and the unit cell volume is... The monoclinic phase with chemical composition SrAl4O7 (JCPDS PDF#70-1749) has space group C2 / c

[15] and lattice constants a, b and c of 13.0389, 9.0113 and 13.0113, respectively. α, β, and γ are 90.0°, 106.7°, and 90.0°, respectively, and the unit cell volume is...

[0085] From the above analysis, it can be seen that Sr 0.5 Al2O 3.56 :Ce 0.04 Its crystal structure is significantly different from that of the monoclinic phase of SrAl4O7 (JCPDS PDF#70-1749) and the monoclinic phase of SrAl2O4 (JCPDS PDF#74-0794).

[0086] Sr 0.5 Al2O 3.56 :Ce0.04 The excitation spectrum of the material is shown in the attached figure. Figure 2 As shown in the figure, the strongest and second strongest excitation peaks of the 363 nm emission band of this material are located at 252 nm and 316 nm, respectively. This indicates that the triclinic Sr... 0.5 Al2O 3.56 :Ce 0.04 The wavelength of its strongest excitation peak perfectly matches the 253.7 nm ultraviolet light emitted by the mercury lamp.

[0087] Tri-phase Sr 0.5 Al2O 3.56 :Ce 0.04 With monoclinic phase Sr 0.94 Al2O4:Ce 0.04 The emission spectra of the control sample under 254 nm ultraviolet light excitation are shown in the figure below. Figure 3 As shown in the figure. It can be seen from the figure that Sr 0.5 Al2O 3.56 :Ce 0.04 The luminescence intensity is much greater than that of the control sample Sr 0.94 Al2O4:Ce 0.04 The luminous intensity of Sr. 0.5 Al2O 3.56 :Ce 0.04 The material's emission spectrum covers the blue-violet region (380–440 nm), the near-ultraviolet region (UVA, 320–380 nm), and the mid-ultraviolet region (UVB, 280–320 nm). The emission spectrum is mainly composed of two short-wavelength emission bands, with peak wavelengths of 299 nm and 363 nm, respectively, with the 363 nm band being dominant. The 299 nm emission band is located in the mid-ultraviolet band. This emission band is extremely rare in the field of luminescent materials.

[0088] Figure 4 Monoclinic Sr detected using an Edinburgh FLS980 fluorescence spectrometer is presented. 0.94 Al2O4:Ce 0.04 The calculated luminescence quantum yield of the control sample is shown in the figure. As can be seen from the figure, the luminescence quantum yield of this material under 254 nm ultraviolet light excitation is 0.09%. This indicates that the monoclinic Sr... 0.94 Al2O4:Ce 0.04 The control sample showed almost no emission when excited by 254 nm ultraviolet light.

[0089] Figure 5 The results show the Sr detected using an Edinburgh FLS980 fluorescence spectrometer. 0.5 Al2O 3.56 :Ce 0.04 The luminescence quantum yield results of the material. As can be seen from the figure, Sr... 0.5Al2O 3.56 :Ce 0.04 The material exhibits a luminescence quantum yield of 82.66% under 254 nm excitation, which is higher than that of monoclinic Sr. 0.94 Al2O4:Ce 0.04 It increased by 918 times compared to 0.09%.

[0090] Combining Table 1 and Figures 2-5 It is concluded that the three-sloping phase Sr 0.5 Al2O 3.56 :Ce 0.04 The material can be efficiently excited by 254 nm ultraviolet light, increasing the luminescence quantum yield from 0.09% for the monoclinic phase to 82.66%. Its luminescence performance in the mid-ultraviolet band is comparable to that of the monoclinic Sr... 0.94 Al2O4:Ce 0.04 44 times.

[0091] Example 2

[0092] A triclinic luminescent material that can be excited by 254 nm ultraviolet light and emit continuous mid-ultraviolet light, its chemical composition is Sr 0.3 Al2O 3.36 :Ce 0.04 The material with this composition can be prepared by following steps 1 to 12 described above. In this embodiment, a hydrogen atmosphere is used, the sintering temperature is 1650℃, and the holding time is 48 hours.

[0093] Tri-phase Sr 0.3 Al2O 3.36 :Ce 0.04 With monoclinic phase Sr 0.94 Al2O4:Ce 0.04 The emission spectra of the control sample under 254 nm ultraviolet light excitation are shown in the figure below. Figure 6 As shown in the figure. It can be seen from the figure that Sr 0.3 Al2O 3.36 :Ce 0.04 The luminescence intensity of the material is much greater than that of the control sample Sr. 0.94 Al2O4:Ce 0.04 The luminous intensity of Sr. 0.3 Al2O 3.36 :Ce 0.04 The emission spectrum covers the blue-violet region (380–440 nm), the near-ultraviolet region (UVA, 320–380 nm), and the mid-ultraviolet region (UVB, 280–320 nm). The material's emission spectrum is mainly composed of two short-wavelength emission bands, with peak wavelengths of 300 nm and 363 nm, respectively, and the 363 nm band is dominant. The 300 nm emission band is located in the mid-ultraviolet band, a very rare feature in the field of luminescent materials.

[0094] Combining Table 1 and Figure 6 It is concluded that Sr 0.3 Al2O 3.36 :Ce 0.04 The material can be efficiently excited by 254 nm ultraviolet light, and its luminescence performance in the mid-ultraviolet band is comparable to that of monoclinic Sr. 0.94 Al2O4:Ce 0.04 64 times.

[0095] Example 3

[0096] A triclinic luminescent material that can be excited by 254 nm ultraviolet light and emit continuous mid-ultraviolet light, its chemical composition is Sr 0.16 Al2O 3.22 :Ce 0.04 The material with this composition can be prepared by following steps 1 to 12 described above. In this embodiment, a hydrogen atmosphere is used, the sintering temperature is 1650℃, and the holding time is 48 hours.

[0097] The chemical composition is Sr 0.16 Al2O 3.22 :Ce 0.04 The X-ray diffraction characteristics of the material (2θ = 25–55°) are shown in the attached figure. Figure 7 As shown in the figure. It can be seen from the figure that Sr 0.16 Al2O 3.22 :Ce 0.04 The X-ray diffraction pattern and chemical composition are SrAl 12 O 19 The X-ray diffraction standard spectra of the hexagonal phase (JCPDS PDF#80-1195) show high similarity; however, at 2θ of 25.6°, 35.2°, 37.8°, 43.4°, and 52.6°, the chemical composition is Sr. 0.16 Al2O 3.22 :Ce 0.04 The X-ray diffraction pattern of the material contains diffraction peaks, while SrAl 12 O 19 The standard diffraction pattern of the hexagonal phase (JCPDS PDF#80-1195) does not have diffraction peaks at these angles.

[0098] After calibration and calculation, the chemical composition disclosed in this invention is Sr. 0.16 Al2O 3.22 :Ce 0.04 The crystal structure of the material belongs to the triclinic crystal system, with space group P1[1], and lattice constants a, b and c are 5.0632, 14.8324 and 14.8324 respectively. α, β, and γ are 62.3°, 108.1°, and 71.1°, respectively, and the unit cell volume is... All diffraction peaks with relative intensities greater than 0.2% matched 100% with the crystal plane indices obtained based on this lattice constant. The chemical composition is SrAl. 12 O 19 The space group of the hexagonal phase (JCPDSPDF#80-1195) is P63 / mmc

[194] , and the lattice constants a, b and c are 5.5666, 5.5666 and 5.5666 respectively. α, β, and γ are 90.0°, 90.0°, and 120.0°, respectively, and the unit cell volume is... As can be seen from the above analysis, although Sr 0.16 Al2O 3.22 :Ce 0.04 The Sr / Al ratio (0.08) is very close to that of SrAl. 12 O 19 The ratio of the two is 0.083, but their crystal structures are significantly different.

[0099] Tri-phase Sr 0.16 Al2O 3.22 :Ce 0.04 With monoclinic phase Sr 0.94 Al2O4:Ce 0.04 The emission spectrum of the control sample under 254 nm ultraviolet light excitation is as follows: Figure 8 As shown in the figure. It can be seen from the figure that Sr 0.16 Al2O 3.22 :Ce 0.04 The luminescence intensity of the material is much greater than that of the control sample Sr. 0.94 Al2O4:Ce 0.04 The emission intensity of the material is [data missing]. The emission spectrum of this material exhibits a single-peak structure with a peak wavelength of 309 nm. This emission peak is located in the mid-ultraviolet region. Therefore, Sr [data missing]. 0.16 Al2O 3.22 :Ce 0.04 The material can emit a broadband mid-ultraviolet light spectrum with a peak wavelength of 309 nm when excited by 254 nm ultraviolet light.

[0100] Sr 0.16 Al2O 3.22 :Ce 0.04 The excitation spectrum of the material is shown in the attached figure. Figure 9 As shown in the figure, the excitation spectrum of this material has an excitation peak at 264 nm, with 254 nm being the short-wavelength end of this excitation peak and a relative intensity of 0.6.

[0101] Combining Table 1 and Figure 8 It is concluded that Sr 0.16 Al2O3.22 :Ce 0.04 The material can be efficiently excited by 254 nm ultraviolet light and its emission band is located in the mid-ultraviolet region. Its luminescence efficiency in the mid-ultraviolet band is comparable to that of monoclinic Sr. 0.94 Al2O4:Ce 0.04 167 times.

[0102] Example 4

[0103] A triclinic luminescent material that can be excited by 254 nm ultraviolet light and emit continuous mid-ultraviolet light, its chemical composition is Sr 0.1 Al2O 3.16 :Ce 0.04 The material with this composition can be prepared by following steps 1 to 12 described above. In this embodiment, a mixture of hydrogen and nitrogen is used, with hydrogen accounting for 5% (by volume). The sintering temperature is 1650°C, and the holding time is 48 hours.

[0104] Tri-phase Sr 0.1 Al2O 3.16 :Ce 0.04 With monoclinic phase Sr 0.94 Al2O4:Ce 0.04 The emission spectrum of the control sample under 254 nm ultraviolet light excitation is as follows: Figure 10 As shown in the figure. It can be seen from the figure that Sr 0.1 Al2O 3.16 :Ce 0.04 The luminescence intensity of the material is much greater than that of the control sample Sr. 0.94 Al2O4:Ce 0.04 The emission spectrum of this material is mainly composed of an emission band with a peak wavelength of 327 nm, covering the near-ultraviolet (UVA, 320–380 nm) and mid-ultraviolet (UVB, 280–320 nm) regions. The mid-ultraviolet band is located at the short-wavelength end of the 327 nm emission band, and the relative luminescence intensity at 320 nm is 0.88. Therefore, Sr 0.1 Al2O 3.16 :Ce 0.04 The material can emit very strong mid-ultraviolet light.

[0105] Combining Table 1 and Figure 10 It is concluded that Sr 0.1 Al2O 3.16 :Ce 0.04 The material can be efficiently excited by 254 nm ultraviolet light, and its luminescence performance in the mid-ultraviolet band is comparable to that of monoclinic Sr. 0.94 Al2O4:Ce 0.04 113 times.

[0106] Example 5

[0107] All materials with the chemical formula Sr x Al y O (1+1.5y+1.5z) :Ce z (0<z<0.05y, 0.04y≤x≤0.25y) prepared by the preparation method disclosed in the present invention belong to the triclinic crystal system. Table 2 lists Ca x Al y O (1+1.5y+1.5z) :Ce z The relationship between the lattice constant of the material and the x / y ratio. It can be seen from Table 2 that when the Ca / Al ratio decreases from 0.2 to 0.04, Ca x Al y O (1+1.5y+1.5z) :Ce z the material still maintains the triclinic structure. Based on this, it can be concluded that all materials with the chemical formula Ca x Al y O (1+1.5y+1.5z) :Ce z (0<z<0.05y, 0.04y≤x≤0.25y) prepared by the preparation method disclosed in the present invention belong to the triclinic crystal system.

[0108] Table 2 Ca x Al y O (1+1.5y+1.5z) :Ce z Relationship between lattice constant of material and x / y ratio

[0109] <![CDATA[Ca 0.97 Al2O4:Ce 0.02 ]]> 0.485 7.9516 9.3269 7.2048 90.0° 108.7° 90.0° 506.0 monoclinic <![CDATA[Ca 0.4 Al2O 3.43 :What 0.02 ]]> 0.2 11.1585 5.9157 7.5202 86.0° 91.6° 104.1° 480.4 Three obliques <![CDATA[Ca 0.2 Al2O 3.23 :What 0.02 ]]> 0.1 12.2453 5.6446 5.2895 56.4° 63.2° 78.0° 271.4 Three obliques <![CDATA[Ca 0.08 Al2O 3.11 :What 0.02 ]]> 0.04 14.7608 5.6435 5.1768 58.3° 53.7° 54.2° 271.2 Three obliques

[0110] A luminescent material with triclinic structure that can be excited by 254 nm ultraviolet light and emit continuous mid-ultraviolet light, with a chemical composition of Ca 0.5 Al2O 3.53 :Ce 0.02 , the material of this composition can be prepared by adopting the foregoing steps 1 to 12. In this embodiment, the atmosphere used is hydrogen gas, the sintering temperature is 1400°C, and the holding time is 5 hours.

[0111] Triclinic Ca 0.5 Al2O 3.53 :Ce 0.02 Compared with the monoclinic control sample Ca 0.97 Al2O4:Ce 0.02 The emission spectra under excitation of 254 nm ultraviolet light are as shown in Figure 11 It can be seen from the figure that Ca 0.5 Al2O 3.53 :Ce 0.02 the luminous intensity of the material is significantly higher than that of the control sample Ca0.97 Al2O4:Ce 0.02 The emission spectrum of this material includes a visible light emission band with a peak wavelength of 411 nm and an ultraviolet light emission band with a peak wavelength of 329 nm, with the 329 nm emission band being dominant. 320 nm is located at the short-wavelength end of the 329 nm emission band, and its relative luminescence intensity is 0.68, i.e., Ca... 0.5 Al2O 3.53 :Ce 0.02 The material can emit strong mid-ultraviolet light when excited by 254 nm ultraviolet light.

[0112] Combining Table 1 and Figure 11 It is concluded that Ca 0.5 Al2O 3.53 :Ce 0.02 The material can be efficiently excited by 254 nm ultraviolet light, and its luminescence performance in the mid-ultraviolet band is comparable to that of monoclinic Ca. 0.97 Al2O4:Ce 0.02 10 times.

[0113] Example 6

[0114] A triclinic luminescent material that can be excited by 254 nm ultraviolet light and emit continuous mid-ultraviolet light, its chemical composition is Ca. 0.3 Al2O 3.33 :Ce 0.02 The material with this composition can be prepared by following steps 1 to 12 described above. In this embodiment, hydrogen atmosphere is used, the sintering temperature is 1550℃, and the holding time is 5 hours.

[0115] Triclinic phase Ca 0.3 Al2O 3.33 :Ce 0.02 Compared with monoclinic sample Ca 0.97 Al2O4:Ce 0.02 The emission spectrum under 254 nm ultraviolet light excitation is as follows: Figure 12 As shown in the figure. It can be seen from the figure that Ca 0.3 Al2O 3.33 :Ce 0.02 The luminescence intensity of the material is much greater than that of the control sample Ca. 0.97 Al2O4:Ce 0.02 The luminous intensity of Ca. 0.3 Al2O 3.33 :Ce 0.02The material's emission spectrum includes an ultraviolet emission band with a peak wavelength of 326 nm and an emission band at 414 nm with a relative intensity of approximately 13%. The mid-ultraviolet band is located at the short-wavelength end of the 326 nm emission band, and the relative luminescence intensity at 320 nm is 0.89. Therefore, Ca... 0.3 Al2O 3.33 :Ce 0.02 The material can emit strong mid-ultraviolet light when excited by 254 nm ultraviolet light.

[0116] Combining Table 1 and Figure 12 It is concluded that Ca 0.3 Al2O 3.33 :Ce 0.02 The material can be efficiently excited by 254 nm ultraviolet light, and its luminescence performance in the mid-ultraviolet band is comparable to that of monoclinic Ca. 0.97 Al2O4:Ce 0.02 131 times.

[0117] Example 7

[0118] A luminescent material with a triclinic structure that can be excited by 254 nm ultraviolet light and emit continuous mid-ultraviolet light has the chemical composition Ca. 0.2 Al2O 3.23 :Ce 0.02 The material with this composition can be prepared by following steps 1 to 12 described above. In this embodiment, a hydrogen atmosphere is used, the sintering temperature is 1600℃, and the holding time is 5 hours.

[0119] Chemical formula Ca 0.2 Al2O 3.23 :Ce 0.02 The Ca / Al ratio (0.100) in the formula is close to that of CaAl. 12 O 19 The ratio in (0.083) is therefore CaAl 12 O 19 The hexagonal phase (JCPDS PDF#84-1613) is used as a reference spectrum (2θ is 25–70°), as shown in the attached figure. Figure 13 As shown.

[0120] from Figure 13 It can be seen that Ca 0.2 Al2O 3.23 :Ce 0.02 The X-ray diffraction pattern of the material exhibits strong diffraction peaks (relative intensities of 3–8%) near 2θ values ​​of 25.6°, 35.2°, 43.3°, 52.5°, 66.5°, and 68.2°, while CaAl 12 O 19The hexagonal phase (JCPDS PDF#84-1613) has no diffraction lines at these angles.

[0121] After calibration and calculation, the chemical composition was determined to be Ca. 0.2 Al2O 3.23 :Ce 0.02 The crystal structure of the material belongs to the triclinic crystal system, with space group P1[1], and lattice constants a, b and c are 12.2453, 5.6446 and 12.2453, 5.6446 and 12.2453, respectively. α, β, and γ are 56.4°, 63.2°, and 78.0°, respectively, and the unit cell volume is... The chemical composition is CaAl 12 O 19 The space group of the hexagonal phase (JCPDS PDF#84-1613) is P63 / mmc

[194] , and the lattice constants a, b and c are 5.5587, 5.5587 and 5.5587, respectively. α, β, and γ are 90.0°, 90.0°, and 120.0°, respectively, and the unit cell volume is... From the above analysis, it can be seen that Ca 0.2 Al2O 3.23 :Ce 0.02 The crystal structure of the material and CaAl 12 O 19 The hexagonal phase (JCPDS PDF#84-1613) is significantly different.

[0122] Triclinic phase Ca 0.2 Al2O 3.23 :Ce 0.02 Compared with monoclinic sample Ca 0.97 Al2O4:Ce 0.02 The emission spectrum under 254 nm ultraviolet light excitation is as follows: Figure 14 As shown in the figure. It can be seen from the figure that Ca 0.2 Al2O 3.23 :Ce 0.02 The luminescence intensity of the material is much greater than that of the control sample Ca. 0.97 Al2O4:Ce 0.02 The luminous intensity of Ca. 0.2 Al2O 3.23 :Ce 0.02 The emission spectrum is mainly composed of an ultraviolet emission band with a peak wavelength of 330 nm. The relative luminescence intensity at 320 nm is 0.74, and Ca... 0.2 Al2O 3.23 :Ce 0.02 The integral area of ​​the material's emission spectrum in the mid-ultraviolet band accounts for approximately 40% of the total integral area.

[0123] Combining Table 1 and Figure 14 It is concluded that Ca 0.2 Al2O 3.23 :Ce 0.02 The material can be efficiently excited by 254 nm ultraviolet light, and its luminescence performance in the mid-ultraviolet band is comparable to that of monoclinic Ca. 0.97 Al2O4:Ce 0.02 166 times.

[0124] Example 8

[0125] A luminescent material that can be excited by 254 nm ultraviolet light and emit continuous mid-ultraviolet light has the chemical composition Ca. 0.08 Al2O 3.11 :Ce 0.02 The material with this composition can be prepared by following steps 1 to 12 described above. In this embodiment, a mixture of hydrogen and nitrogen is used, with hydrogen accounting for 5% (by volume). The sintering temperature is 1650°C, and the holding time is 5 hours.

[0126] Although the chemical formula Ca 0.08 Al2O 3.11 :Ce 0.02 The Ca / Al ratio (0.04) in the formula CaAl is different from the chemical formula CaAl. 12 O 19 The Ca / Al ratios (0.083) differ significantly, however, given that CaAl 12 O 19 The Ca / Al ratio is the smallest among known phases of calcium aluminate, therefore CaAl is still considered the smallest. 12 O 19 The hexagonal phase (JCPDS PDF#84-1613) is used as a reference spectrum (2θ is 5–70°), as shown in the attached figure. Figure 15 As shown.

[0127] from Figure 15 It can be seen that Ca 0.08 Al2O 3.11 :Ce 0.02 The X-ray diffraction pattern of the material exhibits strong diffraction peaks (relative intensities of 30–100%) near 2θ values ​​of 25.6°, 35.2°, 43.3°, 52.5°, 66.5°, and 68.2°, while CaAl 12 O 19 The hexagonal phase (JCPDS PDF#84-1613) exhibits no diffraction lines at these angles. Additionally, CaAl... 12 O 19The hexagonal phase (JCPDS PDF#84-1613) exhibits diffraction peaks of comparable intensity (relative intensity values ​​of approximately 10%) near 2θ values ​​of 8.1°, 16.2°, 20.1°, 22.1°, and 24.4°, while Ca... 0.08 Al2O 3.11 :Ce 0.02 The X-ray diffraction patterns of the material show significant differences in the intensity of the diffraction peaks at these angles (relative intensity values ​​range from 0.2% to 15.6%).

[0128] After calibration and calculation, the chemical composition was determined to be Ca. 0.08 Al2O 3.11 :Ce 0.02 The crystal structure of the material belongs to the triclinic crystal system, with space group P1[1], and lattice constants a, b and c are 14.7608, 5.6435 and 14.7608, 5.6435 and 14.7608, respectively. α, β, and γ are 58.3°, 53.7°, and 54.2°, respectively, and the unit cell volume is... The chemical composition is CaAl 12 O 19 The space group of the hexagonal phase (JCPDS PDF#84-1613) is P63 / mmc

[194] , and the lattice constants a, b and c are 5.5587, 5.5587 and 5.5587, respectively. α, β, and γ are 90.0°, 90.0°, and 120.0°, respectively, and the unit cell volume is... From the above analysis, it can be seen that Ca 0.08 Al2O 3.11 :Ce 0.02 The crystal structure of the material and CaAl 12 O 19 The hexagonal phase (JCPDS PDF#84-1613) is significantly different.

[0129] Ca 0.08 Al2O 3.11 :Ce 0.02 Compared with monoclinic sample Ca 0.97 Al2O4:Ce 0.02 The emission spectrum under 254 nm ultraviolet light excitation is as follows: Figure 16 As shown. From Figure 16 It can be seen that Ca 0.08 Al2O 3.11 :Ce 0.02 The luminescence intensity of the material is much greater than that of the control sample Ca. 0.97 Al2O4:Ce 0.02 The luminous intensity of Ca. 0.08 Al2O 3.11 :Ce 0.02The material's emission spectrum includes an ultraviolet emission band with a peak wavelength of 332 nm, and a sub-emission band with a relative intensity of approximately 0.75 at 345 nm. The mid-ultraviolet band is located at the short-wavelength end of the 332 nm emission band, and the relative luminescence intensity at 320 nm is 0.60. Therefore, Ca... 0.08 Al2O 3.11 :Ce 0.02 The material exhibits a distinct emission spectrum in the mid-ultraviolet light band.

[0130] Combining Table 1 and Figure 16 It is concluded that Ca 0.08 Al2O 3.11 :Ce 0.02 The material can be efficiently excited by 254 nm ultraviolet light, and its luminescence performance in the mid-ultraviolet band is comparable to that of monoclinic Ca. 0.97 Al2O4:Ce 0.02 75 times.

[0131] Example 9

[0132] A luminescent material with a triclinic structure that can be excited by 254 nm ultraviolet light and emit continuous mid-ultraviolet light, its chemical composition is Sr 0.4 Ba 0.1 Al2O 3.56 :Ce 0.04 The material with this composition can be prepared by following steps 1 to 12 described above. In this embodiment, a hydrogen atmosphere is used. The sintering temperature is 1650℃, and the holding time is 48 hours.

[0133] Sr 0.4 Ba 0.1 Al2O 3.56 :Ce 0.04 The X-ray diffraction characteristics of the material (2θ = 5–60°) are shown in the attached figure. Figure 17 As shown. Given that the Sr / Al ratio (0.20) in the sample composition is close to that in SrAl4O7 (0.25), the standard X-ray diffraction pattern of monoclinic SrAl4O7 (JCPDS PDF#70-1479) is used as a reference. Additionally, the standard diffraction pattern of the hexagonal phase of BaAl2O4 (JCPDS PDF#72-0387) is also plotted. Figure 17 middle.

[0134] from Figure 17 It can be seen that the 2θ values ​​corresponding to the 1st, 3rd, 4th, and 6th strong lines of the standard X-ray diffraction spectrum of hexagonal BaAl2O4 (JCPDS PDF#72-0387) are 28.3°, 34.3°, 40.1°, and 57.9°, respectively, and their relative intensities are all greater than or close to 20% (the relative intensity of the 6th strong line is 19.3%). Meanwhile, Sr...0.4 Ba 0.1 Al2O 3.56 :Ce 0.04 The relative intensities of the X-ray diffraction lines in the material at these angles are all less than 5%, therefore, Sr 0.4 Ba 0.1 Al2O 3.56 :Ce 0.04 The X-ray diffraction pattern of the material is significantly different from the standard X-ray diffraction pattern of hexagonal BaAl2O4 (JCPDS PDF#72-0387), indicating that the corresponding crystal structures are completely different.

[0135] The X-ray diffraction standard spectrum of SrAl4O7 monoclinic phase (JCPDS PDF#70-1479) shows 2θ values ​​of 25.1°, 33.8°, and 14.1° for the 1st, 3rd, and 5th intensity lines, respectively, with relative intensities all greater than 30%. Meanwhile, Sr... 0.4 Ba 0.1 Al2O 3.56 :Ce 0.04 The relative intensity of the X-ray diffraction patterns of the material at these angles is less than 2% (no diffraction lines at 14.1°).

[0136] In addition, Sr 0.4 Ba 0.1 Al2O 3.56 :Ce 0.04 The strongest line in the X-ray diffraction pattern of the material corresponds to 2θ at 29.0°, while the standard spectra of hexagonal phase BaAl2O4 (JCPDS PDF#72-0387) and monoclinic phase SrAl4O7 (JCPDS PDF#70-1479) show no diffraction lines at this angle. 0.4 Ba 0.1 Al2O 3.56 :Ce 0.04 The X-ray diffraction patterns of the material clearly show diffraction lines at 2θ of 8.0°, 18.3°, 20.8°, 33.2° and 49.2°, while the standard X-ray diffraction patterns of hexagonal phase BaAl2O4 (JCPDS PDF#72-0387) and monoclinic phase SrAl4O7 (JCPDS PDF#70-1479) show no diffraction lines at these angles.

[0137] After calibration and calculation, the chemical composition disclosed in this invention is Sr. 0.4 Ba 0.1 Al2O 3.56 :Ce 0.04 The crystal structure of the material belongs to the triclinic crystal system, with space group P1[1], and lattice constants a, b and c are 11.6224, 4.9117 and 11.6224, 4.9117 and 11.9117, respectively. α, β, and γ are 114.6°, 96.0°, and 71.0°, respectively, and the unit cell volume is... In addition, the space group of the monoclinic phase with chemical composition SrAl4O7 (JCPDS PDF#70-1749) is C2 / c

[15] , and the lattice constants a, b and c are 13.0389, 9.0113 and 13.0113 respectively. α, β, and γ are 90.0°, 106.7°, and 90.0°, respectively, and the unit cell volume is... The space group of the hexagonal phase BaAl2O4 (JCPDS PDF#72-0387) is P6322

[182] , and the lattice constants a, b and c are 5.2180, 5.2180 and 5.2180, respectively. α, β, and γ are 90.0°, 90.0°, and 120.0°, respectively, and the unit cell volume is...

[0138] From the above analysis, it can be seen that Sr 0.4 Ba 0.1 Al2O 3.56 :Ce 0.04 The structure is significantly different from that of the monoclinic phase SrAl4O7 (JCPDS PDF#70-1479) and the hexagonal phase of BaAl2O4 (JCPDS PDF#72-0387).

[0139] Tri-phase Sr 0.4 Ba 0.1 Al2O 3.56 :Ce 0.04 With monoclinic phase Sr 0.94 Al2O4:Ce 0.04 The emission spectrum of the control sample under 254 nm ultraviolet light excitation is as follows: Figure 18 As shown in the figure. It can be seen from the figure that Sr 0.4 Ba 0.1 Al2O 3.56 :Ce 0.04 The luminescence intensity of the material is much greater than that of the control sample Sr. 0.94 Al2O4:Ce 0.04 The luminescence intensity of Sr. Its emission spectrum consists of a mid-ultraviolet emission band with a peak wavelength of 317 nm and a blue emission band of 459 nm, with ultraviolet emission being absolutely dominant. Since the 317 nm emission band is located in the mid-ultraviolet region, Sr 0.4 Ba 0.1 Al2O 3.56 :Ce 0.04 The material has an independent emission spectrum peak and the strongest luminescence intensity in the mid-ultraviolet band.

[0140] Combining Table 1 and Figure 18 It is concluded that Sr0.4 Ba 0.1 Al2O 3.56 :Ce 0.04 The material can be efficiently excited by 254 nm ultraviolet light, and its luminescence performance in the mid-ultraviolet band is comparable to that of monoclinic Sr. 0.94 Al2O4:Ce 0.04 35 times.

[0141] Example 10

[0142] A luminescent material with a triclinic structure that can be excited by 254 nm ultraviolet light and emit continuous mid-ultraviolet light, its chemical composition is Sr 0.31 Mg 0.14 Al2O 3.51 :Ce 0.04 The material with this composition can be prepared by following steps 1 to 12 described above. In this embodiment, a hydrogen atmosphere is used. The sintering temperature is 1650℃, and the holding time is 48 hours.

[0143] Tri-phase Sr 0.31 Mg 0.14 Al2O 3.51 :Ce 0.04 With monoclinic phase Sr 0.94 Al2O4:Ce 0.04 The emission spectrum of the control sample under 254 nm ultraviolet light excitation is as follows: Figure 19 As shown in the figure. It can be seen from the figure that Sr 0.31 Mg 0.14 Al2O 3.51 :Ce 0.04 The luminescence intensity of the material is much greater than that of the control sample Sr. 0.94 Al2O4:Ce 0.04 The luminescence intensity of Sr is [missing information]. Its emission spectrum consists of an ultraviolet emission band with a peak wavelength of 328 nm. 320 nm is near the center wavelength of the 328 nm emission band, and its relative luminescence intensity is 0.93; moreover, Sr [missing information]. 0.31 Mg 0.14 Al2O 3.51 :Ce 0.04 Approximately 35–40% of the integral area of ​​the material’s emission spectrum is contributed by the emission spectrum in the mid-ultraviolet band.

[0144] Combining Table 1 and Figure 19 It is concluded that Sr 0.31 Mg 0.14 Al2O 3.51 :Ce 0.04 The material can be efficiently excited by 254 nm ultraviolet light, and its luminescence performance in the mid-ultraviolet band is comparable to that of monoclinic Sr. 0.94 Al2O4:Ce0.04 76 times.

[0145] Example 11

[0146] A luminescent material with a triclinic structure that can be excited by 254 nm ultraviolet light and emit continuous mid-ultraviolet light, its chemical composition is Mg. 0.05 Ca 0.14 Sr 0.23 Ba 0.03 Al2O 3.51 :Ce 0.04 The material with this composition can be prepared by following steps 1 to 12 described above. In this embodiment, a hydrogen atmosphere is used, the sintering temperature is 1650℃, and the holding time is 48 hours.

[0147] Triclinic phase Mg 0.05 Ca 0.14 Sr 0.23 Ba 0.03 Al2O 3.51 :Ce 0.04 With monoclinic phase Sr 0.94 Al2O4:Ce 0.04 The emission spectrum of the control sample under 254 nm ultraviolet light excitation is as follows: Figure 20 As shown in the figure. It can be seen from the figure that the control sample Sr... 0.94 Al2O4:Ce 0.04 The luminescence intensity is much smaller than that of Mg 0.05 Ca 0.14 Sr 0.23 Ba 0.03 Al2O 3.51 :Ce 0.04 The material's luminescence intensity. Its emission spectrum exhibits a roughly symmetrical single-peak structure with a peak wavelength of 323 nm. The relative luminescence intensity at 320 nm is 0.98, and approximately 45% of the integrated area of ​​the 323 nm emission band is contributed by the emission spectrum in the mid-ultraviolet band.

[0148] Combining Table 1 and Figure 20 It is concluded that Mg 0.05 Ca 0.14 Sr 0.23 Ba 0.03 Al2O 3.51 :Ce 0.04 The material can be efficiently excited by 254 nm ultraviolet light, and its luminescence performance in the mid-ultraviolet band is comparable to that of monoclinic Sr. 0.94 Al2O4:Ce 0.04 215 times and monoclinic Ca 0.97 Al2O4:Ce 0.02 294 times.

[0149] The above examples are only for illustrating the present invention. In addition, there are many other different implementations, which can be conceived by those skilled in the art after understanding the concept of the present invention. Therefore, they will not be listed one by one here.

Claims

1. A continuous mid-ultraviolet luminescent material, characterized in that, The luminescent material has a triclinic crystal structure and a general chemical formula of M. x Al y O (x+1.5y+1.5z) :Ce z Where M represents a combination of one or more elements selected from Sr, Ca, Ba, or Mg, 0 <z<0.05y,0.04≤(x / y)≤0.25。 2. The continuous mid-ultraviolet luminescent material as described in claim 1, characterized in that, The general chemical formula is M x Al y O (x+1.5y+1.5z) :Ce z Where M represents Sr and / or Ca; or M represents a combination of Sr and / or Ca with Ba and / or Mg, 0 <z<0.05y,0.04≤(x / y)≤0.25。 3. The continuous mid-ultraviolet luminescent material as described in claim 1, characterized in that, The general chemical formula is M x Al y O (x+1.5y+1.5z) :Ce z Where M represents a combination of one or more elements from Ca, Ba, or Mg with Sr, 0 <z<0.05y,0.04≤(x / y)≤0.25。 4. The continuous mid-ultraviolet luminescent material as described in claim 1, characterized in that, The general chemical formula is Sr x Al y O (x+1.5y+1.5z) :Ce z , of which 0 <z<0.05y,0.04≤(x / y)≤0.25。 5. The continuous mid-ultraviolet luminescent material as described in claim 1, characterized in that, When excited by ultraviolet light with wavelengths between 240 and 275 nanometers, it can emit continuous ultraviolet light with wavelengths between 280 and 380 nanometers.

6. The continuous mid-ultraviolet luminescent material as described in claim 1, characterized in that, When excited by ultraviolet light with a wavelength between 240 and 275 nanometers, it can emit continuous mid-ultraviolet light, wherein the continuous mid-ultraviolet light has a significant emission peak in the 280-320 nanometer band; or has a significant emission peak in the 320-335 nanometer band and the relative emission intensity at 320 nanometers reaches more than 60% of the peak intensity of the emission spectrum; wherein the emission spectrum range is 280-480 nanometers.

7. The continuous mid-ultraviolet luminescent material as described in claim 1, characterized in that, When excited by ultraviolet light with a wavelength between 240 and 275 nanometers, it can emit continuous mid-ultraviolet light, which has an independent emission peak in the 280-320 nanometer wavelength range.

8. The method for preparing the continuous mid-ultraviolet luminescent material according to any one of claims 1 to 4, characterized in that, Includes the following steps: Step S1: Prepare a mixture of metal compound powders according to the stoichiometric ratio of the metal elements in the chemical formula; Step S2: Measure an appropriate volume of anhydrous ethanol and pour it into the mixture obtained in step S1. Wet grinding or ball milling with an appropriate proportion of alumina grinding balls for a certain period of time is performed. Then, separation operation is carried out to obtain a slurry of the mixture. The slurry is dried in a drying oven at 100~200℃ for a certain period of time to obtain the mixture before calcination. Step S3: The mixture before calcination is loaded into a corundum crucible and placed in an atmosphere furnace for sintering. During the calcination process, a reducing atmosphere is used for protection, and the sintering temperature is controlled between 1400 and 1700°C. The holding time is controlled between 2 and 48 hours. Step S4: The sintered product is crushed, ground, and sieved through a standard sieve to obtain the continuous mid-ultraviolet light luminescent material.

9. The application of the continuous mid-ultraviolet luminescent material as described in claim 1, characterized in that, It is added to fluorescent material products in powder, bulk, and thin film states.